THE EFFECTIVENESS OF MURABAHAH FINANCING IN IMPROVING THE WELFARE OF MSMES IN BABALAN DISTRICT - Yopi Suhanda; Khairani Sakdiah (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study aims to analyze the effectiveness of murabahah financing in improving the welfare of Micro, Small, and Medium Enterprises (MSMEs) in Babalan District. MSMEs often face financial constraints such as funding mismatches, complicated credit procedures, and high transaction costs. As a solution, the Islamic banking system through murabahah contracts offers a riba-free financing scheme that is considered fairer and safer for small business actors. This research employs a qualitative descriptive approach, utilizing data analysis of MSME income levels. The results indicate that murabahah financing is effective in increasing the income and welfare of MSME actors in Babalan District. Empirical data shows that business owners who utilize murabahah financing—particularly in the culinary, service, and trade sectors—experience more significant income growth compared to those relying solely on personal capital. This increase is driven by additional working capital used for raw materials and business equipment procurement. The study concludes that access to fair Sharia financing is a key factor in encouraging business expansion and the household economic stability of MSME actors at the local level.